CREB-binding protein (CBP) regulates β-adrenoceptor (β-AR)−mediated apoptosis - Lee, Y Y (Nature Publishing Group, 2013)
Catecholamines regulate the β-adrenoceptor/cyclic AMP-regulated protein kinase A (cAMP/PKA) pathway. Deregulation of this pathway can cause apoptotic cell death and is implicated in a range of human diseases, such as neuronal loss during aging, cardiomyopathy and septic shock. The molecular mechanism of this process is, however, only poorly understood. Here we demonstrate that the β-adrenoceptor/cAMP/PKA pathway triggers apoptosis through the transcriptional induction of the pro-apoptotic BH3-only Bcl-2 family member Bim in tissues such as the thymus and the heart. In these cell types, the catecholamine-mediated apoptosis is abrogated by loss of Bim. Induction of Bim is driven by the transcriptional co-activator CBP (CREB-binding protein) together with the proto-oncogene c-Myc. Association of CBP with c-Myc leads to altered histone acetylation and methylation pattern at the Bim promoter site. Our findings have implications for understanding pathophysiology associated with a deregulated neuroendocrine system and for developing novel therapeutic strategies for these diseases.